Frequency and the effects of spondyloarthritis-spectrum disorders on the clinical course and management of Takayasu arteritis: an observational retrospective study - DİRESKENELİ, RAFİ HANER; ALİBAZ ÖNER, FATMA (My University, 2024)
Objectives: Extravascular findings of Takayasu arteritis (TAK) often share features with the spondyloarthritis (SpA) spectrum of disorders. However, the characteristics of this overlap and its effect on the vascular manifestations of TAK are not fully known. Therefore, we aimed to investigate the frequency of SpA-related features in TAK patients. Material and methods: In this observational retrospective study, 350 patients with TAK classified according to ACR 1990 criteria, from 12 tertiary rheumatology clinics, were included and evaluated for the presence of axSpA, IBD, or psoriasis. Demographic, clinical features, angiographic involvement patterns, disease activity, and treatments of TAK patients with or without SpA were analyzed. Results: Mean age was 45.5 ± 13.6 years and mean follow-up period was 76.1 ± 65.9 months. Among 350 patients, 31 (8.8%) had at least one additional disease from the SpA spectrum, 8 had IBD, 8 had psoriasis, and 20 had features of axSpA. In the TAK-SpA group, TAK had significantly earlier disease onset, compared to TAK-without-SpA (p = 0.041). SpA-related symptoms generally preceded TAK symptoms. Biological treatments, mostly for active vasculitis, were higher in the TAK-SpA group (70.9%) compared to TAK-without-SpA (27.9%) (p < 0.001). Vascular involvements were similar in both. Conclusion: Our study confirmed that diseases in the SpA spectrum are not rare in TAK. Vascular symptoms appeared earlier in such patients, and more aggressive therapy with biological agents was required in the TAK-SpA group, suggesting an association between TAK and SpA spectrum. (Table presented.)
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; İmmünoloji ve Romatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Immunology and Rheumatology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ROMATOLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; RHEUMATOLOGY; Romatoloji; Rheumatology; Extravascular findings; Inflammatory bowel diseases; Psoriasis; Sacroiliitis; Spondyloarthritis; Takayasu arteritis